Quantifying the Frictional Forces between Skin and Nonwoven Fabrics - Jayawardana, Kavinda; Ovenden, Nicholas C.; Cottenden, Alan (Frontiers in Physiology, 2017)
When a compliant sheet of material is dragged over a convex surface, the frictional forces generated can be many times greater than they would be for a planar interface. This phenomenon is known to contribute to the abrasion damage to skin often suffered by wearers of incontinence pads and bed/chairbound people susceptible to pressure sores. Experiments that attempt to quantify these forces often use a simple capstan-type equation to obtain a characteristic coefficient of friction. In general, the capstan approach assumes the ratio of applied tensions depends only on the arc of contact and the coefficient of friction and ignores other geometric and physical considerations; this approach makes it straightforward to obtain explicitly a coefficient of friction from the tensions measured. In this paper, two mathematical models are presented that compute the material displacements and surface forces generated by, firstly, a membrane under tension in moving contact with a rigid obstacle and,secondly, a shell-membrane under tension in contact with a deformable convex substrate. The results show that while the use of a capstan equation remains fairly robust in some cases, effects such as the curvature and flaccidness of the underlying body, and the mass density of the fabric can lead to significant variations in stresses generated in the contact region and, thus, the coefficient of friction determined by a capstan model may not be an accurate reflection of the true frictional behaviour of the contact region.